Fidalgos e freires-cavaleiros - José Augusto de Sottomayor-Pizarro; Paula Pinto Costa (Medievalista)
Based on the importance of the Luso-Castilian border in the context of medieval Hispania and its complexity as a political construction, the objective of this reflection is to assess its impact at the level of manorial groups, either secular or ecclesiastical. The way how these social groups had interpreted the frontier is a central issue for this study. Fidalgos and miles Christi, usually called knights in simple terms, had traced similar tendencies for understandable reasons. Fidalgos and miles Christi were part of the medieval elites that boosted the peninsular exchanges, developing frequent trajectories over borders in medieval Hispania. The aristocracy and the friars of the Military Orders, in particular, those from the international Orders, had a very fluid conception of the frontier, to which family and institutional interests were superimposed. The noblemen found in the border crossing a natural mechanism to circumvent some political problems, arising from conflicts with monarchs, or to materialize strategies of power of some lineages with patrimonies constituted long before the creation of the kingdom of Portugal itself. In turn, the friars of the Military Orders were sometimes members of these families, imbued with non-border behaviors, which were reinforced when they professed in multinational institutions, not overlapping with the delimitations of the political and diplomatic border.